Literature reviews: Gender And Rural Development - Hasanati, Surani; Rijanta, R; Pitoyo, AJ (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
The purpose of this paper was to elaborate the gap of gender and rural development from geography perspective based on scientific research literature reviews. Four papers was selected to conduct this literature reviews. There are paper from Jennifer C. Langill, Chetan Choitani, Rosanna Quagliariello and friends, also Tamara Jacka and Sally Sargeson. These journals are interesting because it discusses the conception of empirical-scientific geography model as empirical science. Jennifer C. Langill’s paper offered a conceptual framework for gendered division of labour and gendered livelihoods in rural Amazonia: highlighting how gender roles and gendered livelihoods in rural Amazonia: highlighting how gender roles and livelihood seasonality need to be understood as co-produced. Because gendered livelihoods are further complicated by household composition and life-stage, often over-burdened with productive and reproductive labour. While Chetan Choitani shows the impact of migration of men that include ‘improved autonomy’ and ‘increased responsibility’ for left-behind women, also provide conceptual pathways to understand migration-gender-food security linkages. Rosanna Quagliariello and friends offered solutions for gender mainstreaming in rural area by technocratic regulation, legality, implementation and law enforcement within the framework of gender mainstreaming that ensures the empowerment of women towards gender equality. While Tamara Jacka and Sally Sargeson Discover the highlight of local constructions of gender and representation. Keywords: Gender, Rural Development, Gender and Development, Geography, Literature Review